Motivation in mechanics of materials classes: An experimental approach - Lopes Figueiredo da Silva, Hugo Miguel Andrade; Costa, Manuel João; de Meireles, José Filipe Bizarro (International journal of mechanical engineering education, 2017)
This work presents a novel didactic methodology for the approximation of the students to the subject of Mechanics of Materials, with the aim of improving the understanding of the inertia moment, and its relevance on the mechanical behaviour of structures. The students have grouped on groups of two to three persons. The work consisted in designing the most efficient beam having in mind several design constraints. Tensile tests were performed to determine the relevant material properties. Those were used for the analytic dimensioning of the beams. The aim of the work is to obtain the highest efficiency possible, since it results in the best mark, as possible. The efficiency was measured by the maximum load on experimental bending testing, divided by the mass of the beam. The results, as well as the interest of the methodology are discussed. It is proved that this methodology can be useful for the students to apply theoretical concepts and, at the same time, to give a deeper understanding of real experimental tests.